Effectiveness of planned teaching programme on knowledge regarding poly cystic ovarian disease among adolescent girls of Sursinghdhar, New Tehri, Uttarkhand, India - Joshi, Durga; Bisht, Sonia; Panwar, Shweta; Negi, Priyanka; Dharwan, Aarti; Pal, Arushi; Ramola, Deepika; Nautiyal, Manisha; Adil, Mohmmad; Saklani, Neha; Aggarwal, Rajat; Panwar, Pooja; et al. (International Journal Of Community Medicine And Public Health, 2021)
Background: An experimental study was conducted to evaluate the effectiveness of planned teaching programme on knowledge regarding polycystic ovarian disease (PCOD) among adolescent girls. Methods: The research design adopted for the study was one group pre – test post – test design and approach was educative and evaluative approach. This study was undertaken in village of Sursinghdhar, New Tehri, Uttarakhand, India. The data were collected through the questionnaire method with sample size 60 adolescent girls. Results: Findings related to the assessment of pre-test knowledge regarding PCOD depicted that 48.4% of the respondents had average knowledge while 43.3% had poor knowledge. Only 8.3% had good knowledge regarding PCOD. The pretest mean and Sd was 10.1±4.0. Post-test knowledge regarding PCOD depicted that 81.7% of respondents had good knowledge whereas 16.7% and 1.6% reported average and poor knowledge. The post test mean and SD was 19.0±2.8. Effectiveness of PTP on knowledge regarding PCOD among adolescent girls was calculated by paired t- test; and value was 24.1 with p value of 0.001 (S) at ≤0.05 level of significance. It was highly significant. Chi square test revealed that there was significant association between pre-test knowledge score with age (p value 0.02) and previous knowledge socio-demographic variable p value 0.05 at ≤0.05 level of significance Conclusions: The overall findings of the study clearly shows that the pretest knowledge was very less related to PCOD and there is the statistically enhancement in post-test knowledge after PTP. It reveals that, if the adolescent girls are provided regular awareness programme on PCOD will definitely brief up their knowledge, which in turn to improve the total quality of one’s reproductive health.